The Bario journals lem ayu' ulun - Liew, Suet Fun 1960- (Liew Suet Fun, 2021)
In her early fifties, writer Liew Suet Fun uprooted her life and moved to live in Bario, a community of Kelabit rice farmers and hunter-gatherers in the remote interior mountains of Borneo. What began as a choice for love swiftly transformed into an experience that challenged her long-held beliefs and habits of life. Based on her journals from 2013 to 2016, 'Lem Ayu' Ulun' is a beautifully written and intimate record of her early years in Bario: part reminiscence, part everyday miscellany, part philosophical reflection. It offers a unique portrait of an author's inner world while juxtaposing it with that of an indigenous community which was and remains in the throes of far-reaching change. Both author and community are strangers in strange lands, armed with the realisation that only bitter experience and courage are able to forge reconciliation with the worlds around them. 'Lem Ayu' Ulun' - a Kelabit phrase meaning 'this is life' - is filled with narratives of loss and gain, beginnings and endings, individuality and communality, isolation and comfort, celebration and despair. Liew Suet Fun's voice recognises life's contrasts, and sometimes chaos, as a natural state. This acknowledgement may be the only way we can embrace our existence with some measure of equanimity and grace.